The game meat scheme in South Africa - van der Merwe, Maretha, speaker; Renecker, Lyle, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Over 10,000 privately owned fenced wildlife ranches with 16 million head of game have transformed 25 million ha of marginal agricultural land with limited water into thriving operations with far greater economic output than from cattle livestock enterprises (total head only 14 million). A commercial game ranch generates an economic output of about $31/ha compared to $11/ha for livestock farming and creates better paid jobs for a skilled workforce. Meat production and processing on these ranches offers a practical route to improved food security and economic sustainability while maintaining biodiversity. In the past game ranchers had limited options with regards to the utilization of game meat but this scenario changed when a market demand emerged for organic, natural and healthier protein food. A pro-active initiative from Wildlife Ranching South Africa (WRSA), the official mouthpiece of game ranchers in South Africa produced the Game Meat Scheme that was, only after nine years finally successfully negotiated with SA government in a bid to practically guide the legal provision of safe game meat to the local market. The greatest benefit is the fact that the Scheme places the full financial benefits of game meat into the hands of the game rancher. The required registration of the facility on the farm and the rancher as the game meat examiner (meat inspection) will ensure that safe quality meat is produced and will ensure the SA Game Industry to grow from strength to strength and provide the answer to the escalating protein food shortage.
The economic prospects of game meat production in South Africa
Moderator: Lyle Renecker.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses